Feasibility study of a 100-million gallon ethanol plant in Des Moines, Iowa - Broders, Nathan (Kansas State University, 2010)
The cost of energy is a major concern for the United States and its citizens. With domestic demand at all time highs, the need for renewable fuels has become a key in reducing our countries reliance on imported energy. It is important for the U.S. to examine the feasibility of producing its own energy from renewable resources that can be grown domestically. Along with the potential financial gains from renewable fuels, the ability to control the supply of energy for the U.S. is also very important. With the amount of oil imported by the U.S., the ability to produce more of our nations needs and not be forced to rely on other countries could be important for our country moving forward. With the political unrest in many oil producing areas, the security of energy independence is a goal for the U.S. This study uses United States Department of Agriculture, Pro Exporter, Advance Trading, and other statistical sources to analyze the economic feasibility of an ethanol plant near Des Moines, IA. It looks at the available supply of corn in the area as well as the production of ethanol and distillers grains. An increase in the price of imported oil does not necessarily results in an economically viable ethanol plant. Many variables go into the economic viability of an ethanol plant and consumers will still buy the low cost good, and that may be imported energy. Some of these variables affecting economic viability include corn price and availability, denaturant price, natural gas price, ethanol demand and distillers grains demand. With the push for cleaner air and a cleaner environment, ethanol is also used as a gasoline additive to reduce emissions. As more states regulate a higher inclusion rate of ethanol, this will continue to create greater demand. A 100 million gallon ethanol plant is an economically viable investment in the Des Moines area, but when looking at the sensitivity tests, the better investment option if investors want to enter the ethanol industry, is to buy an existing ethanol plant.
Keywords: Ethanol Plant; Investment Analysis; Net Present Value; Agriculture, General (0473); Economics, Agricultural (0503); Energy (0791)